2030 Agenda for sustainable tourism – The Way of Santiago de Compostela and the Ancient Trasversale Sicula - Guido Cimadomo; Renzo Lecardane; Pietro Maria Torregrossa (Agathón)
Sustainable tourism is a determining factor for territorial rebalancing and inclusive development in rural areas within the Sustainable Development Goals framework outlined in Agenda 2030. This paper employs a comparative methodology to examine two distinct cases: the Way of Santiago de Compostela, which is characterised by structured, multi-level management, and the more informal grassroots initiatives of the Ancient Sicilian Transversal, where governance largely relies on local associations and bottom-up initiatives. This study identifies the challenges and opportunities presented by each pathway, evaluating strategies and integrated interventions to foster architectural projects to achieve economic and social sustainability, widespread accessibility of places, and reduction of inequalities in rural areas.